Equity Crowdfunding (ECF) as A Financial Solution for MSMEs During The Covid-19 Pandemic: An Interdisciplinary Analysis: An Interdisciplinary Analysis - Afra Hanifah Prasastisiwi; Qonita Luthfia Alimah; Derajad Sulistyo Widhyharto (East Java Economic Journal, 2021)
The COVID-19 pandemic has resulted in vulnerable conditions for MSMEs, including the funding aspect. As the largest contributor to the East Java economy, MSMEs must receive more protection, one of which is by selecting the right alternative capital. By combining the results of a literature study and interviewing informants, this paper describes alternative funding solutions as an effort to recover the economy during the pandemic. The results of the interdisciplinary analysis found that the proper alternative funding for MSMEs was Equity Crowdfunding (ECF). ECF is able to attract investors who have both economic and social intentions. Both intentions are considered equally important with the purpose of this alternative funding, namely to establish protection in the capital aspect for MSMEs. In addition, ECF currently has many potentials, especially considering the popularity of millennial investment trends and “hijrah financial”—financial migration to the sharia economy—among Indonesian people. Juxtaposed with the results of interviews, the interdisciplinary analysis is expected to describe the real situation of economic conditions in East Java. Then the output produced by this paper will be in the form of suggestions for MSMEs and the government regarding the use, development, and provision of education related to ECF.